The Incidence of Inguinal hernia recurrence after Laparoscopic herniorrhaphy - a retrospective multicentre cohort study of patients operated on at a private practice in Cape Town - MacGuire, Colin Iain (Department of Surgery, 2015)
Includes bibliographical references.